Caribou reactions to provocation by snowmachines in Newfoundland - Mahoney, S.P.; Mawhinney, K.; McCarthy, C.; Anions, Doug; Taylor, S. (Rangifer, 2001)
Caribou in Gros Morne National Park reacted to provocation by snowmachine with significant differences in their response between years. Upon exposure to snowmachines, caribou were displaced 60 to 237 m from their initial locations. Groups with calves allowed the snowmachines to approach more closely before responding (5 to 600 m) than adult-only groups (30 to 1300 m), and their overall flight distances were less. Time spent in locomotion and overall reaction time were greater for animals engaged in the most sedentary activities (eg. standing; mean = 239 s and mean = 262 s, and lying; mean = 166 s and mean = 273 s) than for animals already engaged in more dynamic activities such as walking (mean = 118 s and mean = 133 s), running (mean = 74 s and mean = 63 s) and feeding (mean = 118 s and mean = 133 s). Annual differences in the response of adult-only groups were not due to differences in the sex ratio of these groups, but may be related to annual variation in winter weather conditions.